Strategi Pengembangan Tabungan iB Ukhuwah melalui Analisis SWOT di PT. BPR Syariah Gunung Slamet Cilacap - Asky Humeriatunnisa; Ega Fransiska; Humamul Hakim; Unfah Ziyan Zuhwa; Sulasih Sulasih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study to analyze the development strategy of the iB Ukhuwah Savings Product at PT. BPR Syariah Gunung Slamet Cilacap using the SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats). The SWOT framework is used tocreate successful development strategies and to determine the internal and external elements that affect a product’s competitiveness. This research adopts approach, using information gathered by direct interviews with the management of PT. BPRS Gunung Slamet. The finding reveal that the main strengths of the product lie in its zero monthly administration fees, compliance with Islamic principles, and an attractive prize draw program for customers. However, several weaknesses are identified, such as the absence of digital banking facilities like ATMs and mobile banking. Opportunities arise from partnerships with schools, Islamic boarding institutions, and local small businesses, while threats include increasing competition from conventional banks and other financial institutions. According to the SWOT assessment, suggested strategies involve improving online banking services, strengthening promotion through social media, expanding institutional collaborations, and improving employee competence to ensure excellent service quality.